Initial analysis of peripheral lymphocytic extracellular signal related kinase activation in autism. (January 2017) - Erickson, Craig A.; Ray, Balmiki; Wink, Logan K.; Bayon, Baindu L.; Pedapati, Ernest V.; Shaffer, Rebecca; Schaefer, Tori L.; Lahiri, Debomoy K.
Abstract: Background: Dysregulation of extracellular signal-related kinase (ERK) activity has been potentially implicated in the pathophysiology of autistic disorder (autism). ERK is part of a central intracellular signaling cascade responsible for a myriad of cellular functions. ERK is expressed in peripheral blood lymphocytes, and measurement of activated (phosphorylated) lymphocytic ERK is commonly executed in many areas of medicine. We sought to conduct the first study of ERK activation in humans with autism by utilizing a lymphocytic ERK activation assay. We hypothesized that ERK activation would be enhanced in peripheral blood lymphocytes from persons with autism compared to those of neurotypical control subjects. Method: We conducted an initial study of peripheral lymphocyte ERK activation in 45 subjects with autism and 26 age- and gender-matched control subjects (total n = 71). ERK activation was measured using a lymphocyte counting method (primary outcome expressed as lymphocytes staining positive for cytosolic phosphorylated ERK divided by total cells counted) and additional Western blot analysis of whole cell phosphorylated ERK adjusted for total ERK present in the lymphocyte lysate sample. Results: Cytosolic/nuclear localization of pERK activated cells were increased by almost two-fold in the autism subject group compared to matched neurotypical control subjects (cell count ratio of 0.064 ± 0.044 versus 0.034 ± 0.031; p = 0.002). Elevated phosphorylated ERK levels in whole cell lysates also showed increased activated ERK in the autism group compared to controls (n = 54 total) in Western blot analysis. Conclusions: The results of this first in human ERK activation study are consistent with enhanced peripheral lymphocytic ERK activation in autism, as well as suggesting that cellular compartmentalization of activated ERK may be altered in this disorder. Future work will be required to explore the impact of concomitant medication use and other subject characteristics such as level of cognitive functioning on ERK activation. Trial Registration: Not applicable.